Novel MET/TIE2/VEGFR2 inhibitor altiratinib inhibits tumor growth and invasiveness in bevacizumab-resistant glioblastoma mouse models. Issue 9 (1st September 2016) - Piao, Yuji; Park, Soon Young; Henry, Verlene; Smith, Bryan D.; Tiao, Ningyi; Flynn, Daniel L.; de Groot, John F.
Abstract: Background: Glioblastoma highly expresses the proto-oncogene MET in the setting of resistance to bevacizumab. MET engagement by hepatocyte growth factor (HGF) results in receptor dimerization and autophosphorylation mediating tumor growth, invasion, and metastasis. Evasive revascularization and the recruitment of TIE2-expressing macrophages (TEMs) are also triggered by anti-VEGF therapy. Methods: We investigated the activity of altiratinib (a novel balanced inhibitor of MET/TIE2/VEGFR2) against human glioblastoma stem cell lines in vitro and in vivo using xenograft mouse models. The biological activity of altiratinib was assessed in vitro by testing the expression of HGF-stimulated MET phosphorylation as well as cell viability after altiratinib treatment. Tumor volume, stem cell and mesenchymal marker levels, microvessel density, and TIE2-expressing monocyte infiltration were evaluated in vivo following treatment with a control, bevacizumab alone, bevacizumab combined with altiratinib, or altiratinib alone. Results: In vitro, HGF-stimulated MET phosphorylation was completely suppressed by altiratinib in GSC17 and GSC267, and altiratinib markedly inhibited cell viability in several glioblastoma stem cell lines. More importantly, in multiple xenograft mouse models, altiratinib combined with bevacizumab dramatically reduced tumor volume, invasiveness, mesenchymal marker expression, microvessel density, and TIE2-expressing monocyte infiltration compared with bevacizumab alone. Furthermore, in the GSC17 xenograft model, altiratinib combined with bevacizumab significantly prolonged survival compared with bevacizumab alone. Conclusions: Together, these data suggest that altiratinib may suppress tumor growth, invasiveness, angiogenesis, and myeloid cell infiltration in glioblastoma. Thus, altiratinib administered alone or in combination with bevacizumab may overcome resistance to bevacizumab and prolong survival in patients with glioblastoma.